Site selection for biogenic reef restoration in offshore environments: The Natura 2000 area Borkum Reef Ground as a case study for native oyster restoration. Issue 11 (12th November 2020) - Pogoda, Bernadette; Merk, Verena; Colsoul, Bérenger; Hausen, Tanja; Peter, Corina; Pesch, Roland; Kramer, Maike; Jaklin, Sandra; Holler, Peter; Bartholomä, Alexander; Michaelis, Rune; Prinz, Katrin
Abstract: 1. According to the EU Marine Strategy Framework Directive (2008/56/EC), marine protected areas (MPA) should contribute to a good environmental status of the Europeans seas. Measures maintaining or restoring a favourable conservation status of protected species and habitats are mandatory according to the EU Habitats Directive (92/43/EEC). 2. Identification of suitable sites for ecological restoration measures within MPAs is a crucial step towards successful conservation and sustainable MPA management. In terms of species restoration, it is important to restore the respective species with the best possible environment for growth, survival, fitness, and successful recruitment. 3. This study provides a comprehensive list of site‐selection criteria for ecological species restoration. Three general categories were chosen: (1) ecological history: evidence for the historical distribution; (2) feasibility of restoration: regulating framework and logistics; and (3) environmental conditions: quality of abiotic and biotic factors. A total of 16 site‐selection criteria were identified and applied to biogenic reef restoration, namely for reefs of the native European oyster Ostrea edulis, in the German Bight. 4. The Natura 2000 area Borkum Reef Ground was identified as a suitable site for oyster restoration. It is one of three MPAs in the German Exclusive Economic Zone of the North Sea, which have been declared as Nature Conservation Areas according to national legislation. The conservation objectives include maintenance or, if necessary, restoration of the habitat type 'reefs'. As a reef‐building species, the European oyster O. edulis is of particular importance for this habitat type in terms of nature conservation. 5. The step by step approach for site selection presented here is applicable for biogenic reef restoration elsewhere. The selected Natura 2000 area showcases the potential role and future perspective of European MPAs with regards to active conservation measures.